Community television: social mobilization to democratize communication - Peruzzo, Cicília (Em Questão, 2009)
Synthesis of a study on community television in Brazil. Based upon bibliographical and documental research, as well as on interviews with coordinators of pioneer community channels, this study aims to identify the forms of popular participation in community channels in the cable television system in Brazil, and also to recover the origins of this type of audio-visual production ever since its street TV format. The conclusion is that through crises, distortions, and advancements, such means of communication represent a significant step in the democratization of the country’s media and in the configuration of a new model of public television.